2021
DOI: 10.3324/haematol.2020.269670
|View full text |Cite
|
Sign up to set email alerts
|

Aging of human hematopoietic stem cells is linked to changes in Cdc42 activity

Abstract: In this study, we characterize age-related phenotypes of human hematopoietic stem cells (HSCs). We report increased frequencies of HSC, HPC and lineage negative cells in the elderly but a decreased frequency of multi-lymphoid progenitors. Aged human HSCs further exhibited a delay in initiating division ex vivo though without changes in their division kinetics. The activity of the small RhoGTPase Cdc42 was elevated in aged human hematopoietic cells and we identified a positive correlation between Cdc42 activity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
27
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 46 publications
(70 reference statements)
5
27
0
1
Order By: Relevance
“…The distribution of Septins in HSCs might therefore be regulated by the interaction of Septins with the Borg family of Cdc42 effector proteins (Sheffield et al , 2003 ; Farrugia & Calvo, 2016 ). We first tested whether a reduction of the elevated activity of Cdc42 in aged HSCs to the level reported for young HSCs with a specific inhibitor of Cdc42 activity termed CASIN (Florian et al , 2012 ; Grigoryan et al , 2018 ; Leins et al , 2018 ; Liu et al , 2019 ; Amoah et al , 2021 ) might influence distribution of Septin2, 6 or 7 in aged LT‐HSCs. Inhibition of Cdc42 activity increased the frequency of aged LT‐HSCs polar for Septin7 to the frequency reported for young LT‐HSCs (Fig 1 C and D) while the distribution of Septin2 and 6 was not affected by CASIN (Fig EV1 K–M).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The distribution of Septins in HSCs might therefore be regulated by the interaction of Septins with the Borg family of Cdc42 effector proteins (Sheffield et al , 2003 ; Farrugia & Calvo, 2016 ). We first tested whether a reduction of the elevated activity of Cdc42 in aged HSCs to the level reported for young HSCs with a specific inhibitor of Cdc42 activity termed CASIN (Florian et al , 2012 ; Grigoryan et al , 2018 ; Leins et al , 2018 ; Liu et al , 2019 ; Amoah et al , 2021 ) might influence distribution of Septin2, 6 or 7 in aged LT‐HSCs. Inhibition of Cdc42 activity increased the frequency of aged LT‐HSCs polar for Septin7 to the frequency reported for young LT‐HSCs (Fig 1 C and D) while the distribution of Septin2 and 6 was not affected by CASIN (Fig EV1 K–M).…”
Section: Resultsmentioning
confidence: 99%
“…The aging‐related changes in HSCs and hematopoiesis are caused by both cell intrinsic alterations in HSCs and extrinsic BM niche factors (Kamminga & de Haan, 2006 ; Geiger et al , 2007 ; Wang et al , 2011 ; Guidi et al , 2017 ; Saçma et al , 2019 ; Mejia‐Ramirez & Florian, 2020 ). An increase in the activity of the small RhoGTPase Cdc42 in aged HSCs causes the reduced frequency of polar HSCs upon aging and is also causative for HSC aging (Florian et al , 2012 ; Grigoryan et al , 2018 ; Leins et al , 2018 ; Liu et al , 2019 ; Amoah et al , 2021 ). Pharmacological attenuation of the aging‐related increase in the activity of Cdc42 by a specific small molecule inhibitor of Cdc42 activity termed CASIN resets the frequency of polar HSCs back to level reported for young HSCs and rejuvenates the function of chronologically aged HSC.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have reported altered frequencies of CD34+ lymphoid progenitors and HSCenriched phenotypes with advanced human age [16][17][18][19] . Therefore, we next asked if there might be specific age-or source-related shifts in the frequency of HSC and progenitor phenotypes across the eight sample groups analyzed here (Figure 2A, B).…”
Section: Resultsmentioning
confidence: 99%
“…Evidence of cell-intrinsic changes during aging include accumulated DNA damage, and metabolic and epigenetic alterations 15 . In contrast, less extensive analyses of BM cells from older humans have reported variably altered frequencies of certain CD34+ subsets with an increased proportion of those bearing an HSC phenotype and a reduced proportion of those with a more lymphoidrestricted phenotype [16][17][18][19] . However, a detailed comparison of the complete human CD34+ compartment in mobilized as well as normal PB and BM for over 7 decades of life has not yet been reported.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Ikonomi et al also retrieved a single state attractor describing the same HSC population in young physiological conditions [5] . The increase in the number of attractors in the network reconstructed for young HSCs might be linked to their ability to promptly respond to stimulation and which is reduced in aged HSCs [60] . Together with our results from the structural analysis ( Fig.…”
Section: Resultsmentioning
confidence: 99%